Global social drama of pandemic and recession - Leonid M. Grigoryev (Население и экономика, 2020)
Global drama of pandemic has caused the deep reduction of consumption of wealthy strata, unemployment and isolation. Huge number of people around the Globe is facing the step back to basic needs by Maslow pyramid: physiological needs and security. Adaptation of people to the new situation goes difficult, while somewhat easier for employed in intellectual activities, primarily for university professors. The exit from recession is still far ahead, and it will depend on the certification of territories, and issue of trust for citizens to start going from their regions. Morals, literature, memories of survival will be close to models of those after the big wars.